Muscle thickness measurements to estimate gluteus mediusand minimus activity levels - Dieterich, Angela; Pickard, Christine; Strauss, Geoff; Deshon, Louise; Gibson, William; McKay, Jan (Churchill Livingstone, 2014)
The clinical assessment of gluteus medius and minimus force sharing requires non-invasive measurements of individual activity levels. Do ultrasound measurements of change of muscle thickness substitute invasive electromyography (EMG)? Isometric hip abduction in 20–80% maximal voluntary isometric contraction (MVIC) was measured using dynamometry, M-mode ultrasound for gluteus medius and minimus thickness and EMG using (1) surface electrodes on gluteus medius, n = 15, (2) fine-wire electrodes in deep gluteus medius and minimus, n = 6. Gluteus medius thickened by 5.0 (SD 2.5) mm at 80% MVIC while gluteus minimus thickness was constant in the surface EMG study and decreased by 1.6 (SD 1.6) mm at the more ventral location in the fine-wire EMG study. Thickness change of gluteus medius enabled prediction of torque (r2 0.66) and of surface EMG amplitude (r2 0.57). Surface EMG enabled higher torque prediction (r2 0.84) than thickness change. Thickness change of gluteus minimus did not enable a practically relevant estimation of torque production. Ultrasound examination revealed a differential thickening behaviour of gluteus medius and minimus which enabled estimation of isometric torque production only for gluteus medius but with lower precision than surface EMG.